Digital Financial Services regulations: Their evolution and impact on financial inclusion in East Africa - Ronald Ochen; Enock Will Nsubuga Bulime (Kenya Bankers Association (KBA), 2023)
Digital Financial Services such as mobile money provides immeasurable benefits for financial inclusion and intermediation in East Africa. In this paper, we use a Fixed Effects panel model and annual data collected from 2007 to 2021 to examine the evolution of Digital Financial Services regulatory frameworks and their effects on conventional banking and Financial Inclusion in East African countries - Kenya, Tanzania, and Uganda. Results indicate that digital financial services regulations positively and significantly affect conventional banking services and mobile money (financial inclusion). Also, during the COVID19 pandemic period when the different governments instituted COVID19 policy response measures in the digital payments space to circumvent the use of cash and physical contact, positively affected digital financial services, thereby enhancing financial inclusion in the region. Also, an increase in lending rates and the consumer price index causes mobile money to decline. Therefore, digital financial services regulations are pivotal in advancing financial inclusion and intermediation through mobile money and conventional banking services in East Africa. Also, Central Banks should be concerned with mobile money in the economy because it forms part of the loanable funds by banks thus, stabilizing lending rates and prices in the economy is crucial for financial inclusion.
Keywords: 330